Effect of cellulose nanofiber-based coating with chitosan and trans-cinnamaldehyde on the microbiological safety and quality of cantaloupe rind and fresh-cut pulp. Part 2: Quality attributes. (July 2021) - Ozturk, Samet; Zhang, Jin; Singh, Rakesh K.; Kong, Fanbin
Abstract: The quality characteristics of fruits and vegetables can be protected with coatings. The presented study aimed to evaluate the effect of cellulose nanofiber (CNF) based coatings with chitosan (CHI) and trans -cinnamaldehyde (TC) on the quality attributes, including weight loss, total soluble solid (TSS) content, firmness, and color of whole and fresh-cut cantaloupe during storage at 22 °C and 4 °C, respectively. Results showed that CNF-based coating was effective in protecting whole cantaloupes from firmness reduction and color change in redness/greenness ( a* ) and yellowness/blueness ( b* ) during room-temperature storage for up to 11 days. Coating containing only CNF was not able to prevent the quality changes of fresh-cut cantaloupe during the cold storage, but CNF + CHI/CNF + CHI + TC significantly decreased the weight loss, decelerated the firmness increase and maintained the lightness ( L* ) of fresh-cut cantaloupe for up to 7 days. The incorporation of chitosan (1%, w/w) improved the protection effect of CNF-based coatings against quality changes during storage for both whole and fresh-cut cantaloupes, but TC (1%, w/w) did not show significant enhancement on the protection effects of coatings for most quality attributes. This study indicates that the CNF-based coatings have the potential to maintain quality attributes of whole and fresh-cut fruits during storage and distribution. Highlights: CNF-based coating was used to extent self-life of whole and fresh-cut cantaloupes. CHI improved protection effect of CNF-based coating against quality evolutions. CNF-based coatings delayed changes in firmness, a* and b* of whole cantaloupe. CNF+CHI/CNF+CHI+TC delayed changes in firmness, weight loss and L* of fresh-cut cantaloupe.